Gravitation and Astrophysics 2006
DOI: 10.1142/9789812772923_0020
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy quantum gravity

Abstract: If gravitons are super-strong interacting particles and the lowtemperature graviton background exists, the basic cosmological conjecture about the Dopplerian nature of redshifts may be false. In this case, a full magnitude of cosmological redshift would be caused by interactions of photons with gravitons. Non-forehead collisions with gravitons will lead to a very specific additional relaxation of any photonic flux. It gives a possibility of another interpretation of supernovae 1a data -without any kinematics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The main conjecture of this approach about the quantum nature of redshifts may be verified in a ground-based laser experiment. To do it, one should compare spectra of laser radiation before and after passing some distance l in a high-vacuum tube [2]. The temperature T of the graviton background coincides in the model with the one of CMB.…”
Section: How To Verify the Quantum Redshift Mechanismmentioning
confidence: 99%
“…The main conjecture of this approach about the quantum nature of redshifts may be verified in a ground-based laser experiment. To do it, one should compare spectra of laser radiation before and after passing some distance l in a high-vacuum tube [2]. The temperature T of the graviton background coincides in the model with the one of CMB.…”
Section: How To Verify the Quantum Redshift Mechanismmentioning
confidence: 99%
“…In my model of low-energy quantum gravity [1,2], gravity is considered as the screening effect. It is suggested that the background of super-strong interacting gravitons exists in the universe.…”
Section: Introductionmentioning
confidence: 99%